A technology assessment on the capabilities of ABS-CBN corporation and information technology division toward digital convergence - Abarra, Geraldine De Leon (Quezon City Technology Management Center, University of the Philippines Diliman, 2010)
ABS-CBN Corporation (ABS-CBN) is the largest integrated media and entertainment company in the Philippines. The organization is transitioning from broadcast media to multi-media. The Information Technology Division plays an important role in this digital convergence. This paper studies the trends toward digital convergence and analyzes the barriers that ABS-CBN Corporation and IT Division should overcome to meet the strategic objective of achieving digital convergence. This paper concludes with recommendations and scenarios toward digital synergy.
In partial fulfillment of the requirements in TM 299.2
Thesis
Keywords: ABS-CBN.; Technology assessment; Information technology; Digital convergence